An Assessment of the Behavioural Performance of Youth Football Coaches at Academies in the City of Samarra - Mustafa Ahmed Abdul-Majid Al-Samarrai (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The present study aimed to identify the reality of coaching behaviours among youth football academy coaches in the city of Samarra using the Coaching Behaviour Analysis System (CBAS) developed by Smith et al (1977), as one of the standardised scientific systems for analysing coaching behaviour within sporting environments. The researcher adopted a descriptive approach using structured observation. The research sample consisted of eight coaches working at private football academies in the city of Samarra. Two training sessions were filmed for each coach, totalling 16 training sessions, with each session lasting 40 minutes. The study used three high-resolution digital cameras to document the training sessions, after which the coaching behaviours were analysed according to the behavioural categories adopted in the CBAS system. A 5-second time interval was adopted during the behavioural coding process, after which the data was organised and analysed using frequencies, percentages and Z-scores to identify the polarity and trends of the behaviours. The results also showed that the general technical instructions category recorded the highest frequency of occurrence among training behaviours, followed by the organisation and management category, indicating that trainers focused heavily on technical and organisational aspects during the training sessions. The results also showed a relative increase in positive reinforcement and general encouragement behaviours, compared to a clear decrease in punitive and negative behaviours such as punishment, punitive instructions and ignoring mistakes. The study concluded that the training environment within football academies in the city of Samarra tends towards the use of supportive and positive coaching behaviours rather than negative and punitive ones. The study recommended the need to employ standardised behavioural observation systems in the assessment of coaching performance, as well as the development of training programmes for age-group coaches, thereby contributing to improving the quality of coaching interaction within sports academies.